Recent Advances in Y6‐Based Semiconductors: Performance in Solar Cells, Crystallography, and Electronic Structure. Issue 5 (23rd March 2021) - Li, Xuena; Lu, Haipeng; Zhu, Weigang
Abstract: The advent of crescent‐shaped Y6 and its derivatives have recently enabled exceptionally high solar cell performance metrics, for structural, physical, and transport characteristics that remain poorly understood. Here we summarize recent progress on crystallography, electronic structure, and device performance of this kind of non‐fullerene acceptors. First, we discuss molecular engineering and the crystal structure of Y6 and its derivatives. Second, we present theoretical modeling of the molecular orbitals, reorganization energy, and electronic couplings. Third, we summarize single carrier diode and solar cell performance, and discuss the correlations between crystal structure and computational insights. Finally, we discuss unsolved problems and future developments in this field. Overall, this Minireview summarizes crystal structure, computational understanding, and device metrics, thus providing an outlook for future organic semiconductors design and mechanistic studies in fundamental research and industrial applications. Abstract : Why Y6 ? The advent of crescent‐shaped Y6 and its derivatives have recently enabled exceptionally high solar cell performance metrics With Minireview discusses recent advances in the crystal structures, theoretical understanding, SCLC mobility, and PCE of Y6‐based semiconductors, and provides an outlook for future materials design, mechanism study, and device optimization.